2019
DOI: 10.3390/ijms21010112
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Stability of Viral and Viral-Cellular Fusion Transcripts in HPV-Induced Cervical Cancers

Abstract: HPV-DNA integration results in dysregulation of viral oncogene expression. Because viral-cellular fusion transcripts inherently lack the viral AU-rich elements of the 3’UTR, they are considered to be more stable than episome-derived transcripts. The aim of this study is to provide formal proof for this assumption by comparing the stability of viral early transcripts derived from episomal and integrated HPV16 DNA, respectively. Full-length cDNA of three fusion transcripts comprising viral and cellular sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This is considered an important molecular event in cervical carcinogenesis 12 14 . Upon integration, deregulated expression of viral oncogenes E6 and E7 is frequently observed, which may result from the disruption of their negative regulators E1 and/or E2 15 , and the increased stability of E6 and E7 mRNAs expressed from the viral-host fusion transcripts 16 , 17 . Of note, a study also showed that there was no significant association between the expression levels of viral oncogenes and the physical state of the viral genome based on cervical biopsy materials, implying that the constitutive expression rather than the expression level of viral oncogenes seems to play a decisive role in the transformation and the maintenance of malignant phenotype 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This is considered an important molecular event in cervical carcinogenesis 12 14 . Upon integration, deregulated expression of viral oncogenes E6 and E7 is frequently observed, which may result from the disruption of their negative regulators E1 and/or E2 15 , and the increased stability of E6 and E7 mRNAs expressed from the viral-host fusion transcripts 16 , 17 . Of note, a study also showed that there was no significant association between the expression levels of viral oncogenes and the physical state of the viral genome based on cervical biopsy materials, implying that the constitutive expression rather than the expression level of viral oncogenes seems to play a decisive role in the transformation and the maintenance of malignant phenotype 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of integration sites are transcriptionally active, however, different patterns of DNA and RNA integration breakpoints have been noticed [ 56 ]. Importantly, expression of viral-cellular transcripts increases stability of HPV oncogenes [ 57 , 58 ]. HPV integrations exhibit features of enhancers or activators of flanking genes that can act on their target genes over long distances [ 59 , 60 ].…”
Section: Pathogenesis Of Cervical Cancer and Its Precursor Stagesmentioning
confidence: 99%